Magic and rationality in ancient Near Eastern and Graeco-Roman medicine - Horstmanshoff, H. F. J.; Stol, Marten.; Tilburg, C. R. van (Studies in Ancient Medicine, 2004)
For the first time, medical systems of the Ancient Near East and the Greek and Roman world are studied side by side and compared. Early medicine in Babylonia, Egypt, the Minoan and Mycenean world; later medicine in Hippocrates, Galen, Aelius Aristides, Vindicianus, the Talmud. The focus is the degree of \'rationality\' or \'irrationality\' in the various ways of medical thought and treatment. Fifteen specialists contributed thoughtful and well-documented chapters on important issues.